2006
DOI: 10.1021/jp060266d
|View full text |Cite
|
Sign up to set email alerts
|

New Route to Synthesize Highly Active Nanocrystalline Sulfated Titania−Silica:  Synergetic Effects between Sulfate Species and Silica in Enhancing the Photocatalysis Efficiency

Abstract: A simple and efficient approach has been set up for fabricating highly active sulfated titania-silica (SO(4)(2-)/TiO(2)-SiO(2)): Ti(SO(4))(2) was hydrolyzed in the presence of silica, making it possible to sulfate titania and form titania-silica mixed oxide in one step. This study was focused on investigating the roles of sulfate species and silica in improving the physicochemical properties and photoactivity of SO(4)(2-)/TiO(2)-SiO(2) through comparison with sulfated titania (SO(4)(2-)/TiO(2)) and sulfate-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…It could be tted into Ti-O (529.6 eV), Si-O (530.4 eV) and oxygen vacancy (531.6 eV), respectively. 36,37 The result further conrmed that oxygen vacancies formed together with Ti 3+ states, i.e., both of them coexisted in the black Ti-Si-O nanotubes.…”
mentioning
confidence: 83%
“…It could be tted into Ti-O (529.6 eV), Si-O (530.4 eV) and oxygen vacancy (531.6 eV), respectively. 36,37 The result further conrmed that oxygen vacancies formed together with Ti 3+ states, i.e., both of them coexisted in the black Ti-Si-O nanotubes.…”
mentioning
confidence: 83%
“…This can be attributed to the fact that V and S ions are incorporated into the HTS lattice and influence the local chemical state of Ti 4+ ions. It is obvious that the Ti2p region of VOSO 4 -modified HTS can be resolved into three parts, one at 460.1 eV originating from Ti 4+ species, the second at 459.2 eV resulting from VOSO 4 -modified HTS combined with the surface sulfate species [42], and the third at 457.2 eV corresponding to Ti 3+ species. As a result, the reduction of these Ti 4+ to Ti 3+ in the framework with tetrahedral coordination indicates that oxygen vacancies can be created by V and S doping.…”
Section: Chemical State Of Modified Hts Catalystsmentioning
confidence: 99%
“…Yang et al have reported that the sulfate species and silica species could work together to increase the acidity and catalytic activity of SO 4 2-/TiO 2 catalyst. 13 Thus, it can be concluded that the sulfate species and phosphorus species may also have the similar synergetic effects, which is responsible for the high catalytic activity of SO 4 2-/TiO 2 -P catalyst. Due to the disfavored kinetics of the biphasic catalytic system, the heterogeneous catalyst usually was not as active as the homogeneous catalyst.…”
Section: Acetalization Catalyzed By Somentioning
confidence: 96%